Exploring Environmental Factors for the Sports Clusters Development - ABDRASSILOV, Agybay; ORYNBASSAROVA, Yerkenazym; TVARONAVICIENE, Manuela (Journal of Environmental Management and Tourism, 2023)
The development of a sports cluster is an important social task, the solution of which contributes not only to the balance of the local economy, but also to the involvement of the most progressive segments of the population in entrepreneurial activities, tending to a proper lifestyle and active leisure. The growth of entrepreneurial activity in this segment of the economy is determined by many factors, including the state policy for the development of sports and tourism. As a global industry, sport is a potentially significant contributor to climate change, both through carbon emissions and through its impact on sustainable development practices. The purpose of the study is to explore environmental factors influencing the development of the sports cluster in the Kazakhstan and further prospects for its development using forecasting and modelling methods. The environmental policy of the sports movement must be carried out within the broader framework of sustainable development. The environmental work of the sports movement is currently focused on the protection and management of resources and the natural environment in order to improve social and economic conditions. All this should be aimed at education on environmental issues and specific measures for its protection.